2011
DOI: 10.1038/npre.2011.6692.1
|View full text |Cite
|
Sign up to set email alerts
|

Precise Molecular Structures of Cysteine, Cystine, Hydrogen-Bonded Dicysteine, Cysteine Dipeptide, Glutathione and Acetyl Cysteine Based on Additivity of Atomic Radii

Abstract: Structures of molecules are usually represented by arbitrary line drawings, ball and stick or space filling models. In recent years, the author found that on using the appropriate radii of atoms and ions, bond lengths in inorganic, organic and biomolecules and of hydrogen bonds are exact sums of the radii of the adjacent atoms and or ions. This additivity of atomic radii was shown to hold also for the bond lengths in the twenty essential amino acids. On this basis, the atomic structures of the very important m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 10 publications
1
7
0
Order By: Relevance
“…These results suggest that the helical geometry, and not only chirality by itself, may also be needed for the emergence of unconventional superconductivity. However, we cannot rule out at this stage that the absence OP change is due to the shorter length of the cysteine molecules (~0.7nm [56]) compared to the alpha-helix polyaniline molecules (3 nm). Further studies are needed in order to resolve this issue.…”
Section: Bilayersmentioning
confidence: 93%
“…These results suggest that the helical geometry, and not only chirality by itself, may also be needed for the emergence of unconventional superconductivity. However, we cannot rule out at this stage that the absence OP change is due to the shorter length of the cysteine molecules (~0.7nm [56]) compared to the alpha-helix polyaniline molecules (3 nm). Further studies are needed in order to resolve this issue.…”
Section: Bilayersmentioning
confidence: 93%
“…However, the relative thicknesses should be much more accurate. Since these thicknesses are in the order of the molecular dimensions (6.6 Å × 7.1 Å), this indicates that the coverage is approximately one monolayer.…”
Section: Methodsmentioning
confidence: 99%
“…The molecular structure of L‐cysteine with the respective bond lengths is shown in Figure 1. Based on the additivity of covalent atomic radii in bond lengths, the L‐cysteine molecule has approximate dimensions of 6.6 × 7.1 Å 6 . It has been reported that L‐cysteine anchors to the metal surface using either chemisorption (similar to thiolate–metal bonding) or physisorption (similar to the bonding to metal surfaces by the amino and carboxyl functional groups).…”
Section: Introductionmentioning
confidence: 99%
“…Based on the additivity of covalent atomic radii in bond lengths, the L-cysteine molecule has approximate dimensions of 6.6 Â 7.1 Å. 6 It has been reported that Lcysteine anchors to the metal surface using either chemisorption (similar to thiolate-metal bonding) or physisorption (similar to the bonding to metal surfaces by the amino and carboxyl functional groups). Several experimental and theoretical research studies have been conducted previously to elucidate the absorption behaviors of L-cysteine on different metals, and according to them, the L-cysteine adsorption on metallic surfaces is very strong due to the multifunctional anchoring behavior.…”
mentioning
confidence: 99%
See 1 more Smart Citation